Microedus LeConte, 1874 (Coleoptera: Staphylindae: Omaliinae: Anthophagini), a new genus for the Palaearctic Region - Shavrin, Alexey V. (Zootaxa, 2024)
The genus Microedus LeConte, 1874 (Omaliinae: Anthophagini), previously known only from North America, is recorded for the Palaearctic fauna for the first time. Two palaearctic genera were synonymized with Microedus: Altaiodromicus Zerche, 1992 syn. n. and Liophilydrodes Nakane, 1983 syn. n. (replacement name for Lioplax Nakane & K. Sawada, 1956). The genus Microedus was redescribed, illustrated and its taxonomic relations with other genera of the Hygrogeus group are briefly discussed. Four species are (re-)described and illustrated: M. brevitarsis (Champion, 1925) comb. n. (from Geodromicus) (India: Uttarakhand), M. kastcheevi sp. n. (Altai and Dzhungar mts., eastern Kazakhstan), M. schilenkovi (Zerche, 1992) comb. n. (from Altaiodromicus) (Russia (Altai), Kazakhstan), and M. subtilis (Sharp, 1889) comb. n. (from Liophilydrodes) (Russia, Japan). An additional species from Kashmir remains unnamed due the absence of a male, and is compared with the Himalayan M. brevitarsis. A lectotype is designated for Anthophagus subtilis Sharp, 1889. Several new additional combinations are proposed (all these species were previously attributed to the genus Liophilydrodes): M. flavipennis (Watanabe, 1990) comb. n., M. pullus (Nakane & K. Sawada, 1956) comb. n., M. puncticollis (Nakane & K. Sawada, 1956) comb. n., M. suzukii (Watanabe, 1990) comb. n., and M. yamanakai (Watanabe, 1990) comb. n. The following new synonymies are established: M. subtilis = L. subtilis iturupensis Lafer, 2004 syn. n., = L. troglophilus Nakane & K. Sawada, 1956 syn. n. A key to Palaearctic species of Microedus is provided. Mouthparts and the aedeagus of the Nearctic M. austinianus LeConte, 1874 are illustrated for the first time. A distributional map of Microedus from Middle Asia is provided. Microedus schilenkovi is recorded from Kazakhstan for the first time. A checklist of the genus is presented. The genus Microdeus currently contains 16 species, seven in the Nearctic and nine in the Palaearctic Region.